The Prevalence of Metabolic Syndrome and Different Obesity Phenotype in Iranian Male Military Personnel. (March 2017) - Payab, Moloud; Hasani-Ranjbar, Shirin; Merati, Yaser; Esteghamati, Alireza; Qorbani, Mostafa; Hematabadi, Mahboobeh; Rashidian, Hoda; Shirzad, Nooshin
Obesity, especially when concentrated in the abdominal area, is often associated with the presence of metabolic syndrome. Stress, particularly occupational stress, is one of the most important factors contributing to the increased prevalence of metabolic syndrome components among different populations. This study aimed to investigate the prevalence of overweight and obesity as well as the criteria for metabolic syndrome and its risk factors and different obesity phenotype in a population of military personnel aged 20 to 65 years. This study is a retrospective cross-sectional study in which data are extracted from the database of a military hospital (2, 200 participants). The records of participants contained information such as age, marital status, educational level, weight, height, body mass index, blood pressure, waist circumference, history of drug use and smoking, as well as the results of tests including lipid profile and fasting blood glucose. The Adult Treatment Panel III criteria as well as two national criteria were used to identify metabolic syndrome among participants. Data analysis was p1erformed using SPSS version 16. The average age of participants was 33.37 (7.75) years. The prevalence of metabolic syndrome according to Iranian cutoff was 26.6% for the waist circumference >90 cm (585 persons) and 19.6% for the waist circumference >95 cm (432 persons). The rate of metabolic syndrome was identified as 11.1% (432 cases) according to Adult Treatment Panel III criteria. Results of the current study identified that the prevalence of metabolic syndrome among military individuals is less than other populations, but the prevalence of the syndrome is higher than other military personnel in other countries.